Removal of rebar stacked at the west of the engineer office - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the removal of rebar stacked at the west of the engineer office of BRACU new campus development project.